EEG-based emotion recognition in the investment activities - Mat Razi, Nurul Izzati; Othman, Marini; Yaacob, Hamwira Sakti (The Institute of Electrical and Electronics Engineers, Inc., 2016)
Emotion plays a significant role during a decision making process and greatly influence investor's behavior. This paper investigates investors' emotional perception and exemplify how these emotions may affect their judgement in investment activities. In our experiments, the participants' emotion were derived from electroencephalogram (EEG) while they were trading in the stock market. A negative emotion can reduce the rationality of the investor in decision making and lead them to lose money. However, positive emotion can help them to minimize the risk of negative consequences. Based on the EEG-based emotion recognition, this paper presents the result of an investor that was influenced by their emotion and behaviors while making an investment decisions.